THE RELATIONSHIP BETWEEN GIVING MOTIVATION BY TEACHERS TOWARD STUDENT LEARNING OUTCOME IN GEOGRAPHIC LESSONS IN CLASS XI IPS SANGGAU REGENCY - Wiwik Cahyaningrum; Novita Sariani; Sri Rahayu (GeoEco, 2019)
The purpose of this research is to know the effect of giving corrective feedback on homework in the geography lesson on atmospheric material on the result of student learning of class X Madrasah Aliyah Negeri 1 Pontianak. Experimental research consisting of 2 classes, namely experimental class (XE) and control class (XC). Each class is given different treatment in the experiment class given corrective feedback while the control class is not given corrective feedback. Data collection techniques used in the study of measurement techniques and direct observation. The tools used in the collection of research data are test results and observation guidelines. The data analysis technique using the formula of mean and normality test with Shapiro wilk and liliefor test (adaptation of kolmogorof sminorv), t-test and effect size analysis. The research was conducted in class X Madrasah Aliyah Negeri 1 Pontianak. The population of the study were 272 students, the sample of the study was using the technique of proposive class sampling, as many as 2 classes. Giving corrective feedback has a high effect on the learning outcomes of students of class X Madrasah Aliyah Negeri 1 Pontianak with an effect size of 1.8.